Security Infrastructure Service and Information Security Management Capability Audit to Improve System Security in Preventing Cyber Attacks using COBIT 2019 - Salim Salim; Alva Hendi Muhammad (G-Tech: Jurnal Teknologi Terapan, 2025)
Cyber-attacks have become a serious concern in recent years, as hackers can attack systems, databases, and even steal personal data from a particular organization's database and sell it on the dark web. The individual identity data will be used to carry out various financially profitable activities such as online fraud, selling data containing detailed account information, and asking for ransom from data owners. The failure of an organization to protect data assets from cyber-attacks stems from several internal factors such as the vulnerability of the information security system it has, the less than optimal awareness of users in the organization of the importance of maintaining safe behavior in cyberspace, and routine processes related to information security that are missed. COBIT 2019 can be used as an audit framework to assess the level of maturity of the governance. Network infrastructure services in an organization can be measured in terms of the level of capability in terms of the application of technology assets and their configuration using the DSS05 and APO13 domains. This study aims to provide guidelines in assessing system security infrastructure in IT governance by assessing areas that are still not comply with the framework used, and providing recommendations for improving these inconsistencies so that the level of infrastructure capability will be maximized then.